Regional features of the epidemiology of pterygium in the Republic of Bashkortostan - M. M. Bikbov; V. K. Surkova; R. A. Kazakbaev (Acta Biomedica Scientifica, 2022)
Background. Pterygium is ubiquitous and multifactorial; today, information on  the  prevalence of pterygium, risk factors, the relationship of its development with concomitant pathology and the type of life activity of patients in various regions of Russia is limited. All of the above led to the conduct of this epidemiological study in the Republic of Bashkortostan.The aim of the study: to study the prevalence of pterygium, as well as to identify the relationship of risk factors for its development with the type of life activity and concomitant diseases in the urban and rural population of the Republic of Bashkortostan.Methods. On the basis of the Ufa Research Institute of Eye Diseases, within the framework of the Ural Eye and Medical Study (UEMS) research project, a population study of people living in urban and rural regions of the Republic of Bashkortostan was carried out. The study involved 5899  people, including men – 43.7  % (2585  people), women – 56.3 % (3314 people), urban residents made 42.3 % (2491 people), rural – 57.7 % (3408 people).Results. As a result of our study, pterygium was diagnosed in 138 people (204 eyes – 2.3 %) (95% CI: 2.0–2.7 %). One-way analysis showed a higher prevalence of pterygium associated (p˂0.10) with a number of systemic and ophthalmic parameters. However, according to the results of multivariate analysis, it was revealed that the prevalence of pterygium was significantly associated with older age (p = 0.006), rural area of residence (p = 0.001) and low educational level (p = 0.03).Conclusion. The prevalence of pterygium in Republic of Bashkortostan according to the UEMS study was 2.3 %, or 23 people per 1000 population among people over 40 years old. The nature of the settlement influences the prevalence of pterygium in  the Republic of Bashkortostan. Pterygium was more common among older people among all respondents who took part in the study. In the study, pterygium was not a biomarker of general somatic diseases.